Respuesta :

Answer:

x = 7

Explanation:

Simplifying

11x + 13 = 12x + 6

Reorder the terms:

13 + 11x = 12x + 6

Reorder the terms:

13 + 11x = 6 + 12x

Solving

13 + 11x = 6 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.

13 + 11x + -12x = 6 + 12x + -12x

Combine like terms: 11x + -12x = -1x

13 + -1x = 6 + 12x + -12x

Combine like terms: 12x + -12x = 0

13 + -1x = 6 + 0

13 + -1x = 6

Add '-13' to each side of the equation.

13 + -13 + -1x = 6 + -13

Combine like terms: 13 + -13 = 0

0 + -1x = 6 + -13

-1x = 6 + -13

Combine like terms: 6 + -13 = -7

-1x = -7

Divide each side by '-1'.

x = 7

Simplifying

x = 7

Answer:Simple and best practice solution for 11x+13=12x+6 equation. ... + 6 Reorder the terms: 13 + 11x = 6 + 12x Solving 13 + 11x = 6 + 12x Solving for variable 'x'.

Explanation: